Exploring adolescent girls' involvement in decision-making processes regarding child marriage: A systematic review - Wahyuningsih, Sri; Widati, Sri; Puspitasari, Nunik; Salim, Lutfi A.; Azkiya, Mohammad W. (Narra Sains Indonesia, 2025)
Child marriage often involves adolescents aged 10–19 years and poses significant health risks and challenges to gender equality. The aim of this systematic review was to examine the involvement of adolescent girls in decision-making processes regarding child marriage and identify influencing factors. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, this review covered studies published between January 2014 and July 2024. The databases searched included ScienceDirect, Springer Link, PubMed, and Taylor & Francis, using terms related to adolescent girls, decision-making, and child marriage. Inclusion criteria targeted studies involving girls aged 10–19, with methods including qualitative, quantitative, longitudinal, and mixed-method, published in English. Data extraction and quality assessment followed the standards of the Joanna Briggs Institute. Of 6,967 articles, 29 met the inclusion criteria, spanning 26 countries across three continents, with 51.7% being qualitative studies. Economic pressure was identified as the primary driver of child marriage, with significant parental and community influences restricting the girls' decision-making autonomy. Parents, especially fathers, often force girls into marriage to reduce economic burdens and enhance family honor. Some adolescent girls initiate marriage to escape adverse home conditions or societal stigma. Education and strong family support emerged as protective factors, while entrenched social norms perpetuated early marriages. Comprehensive approaches including educational improvement, economic support, and social norm transformation are essential. Addressing child marriage requires multidimensional strategies, encompassing enhanced educational opportunities, economic support, and changing entrenched social norms. Future research should focus on interventions that boost adolescent girls' life skills and decision-making autonomy to delay marriage and enable informed choices.